CUSTOMER SATISFACTION AS THE MODERATING VARIABLE OF CUSTOMER LOYALTY OF INDIHOME CUSTOMERS - PRAMONO HARI ADI; MOCH IQBAL DHIAULHAQ; WENI NOVANDARI (Faculty of Economics and Business, Jenderal Soedirman University, 2019)
The internet is an aspect that become one in the daily activities of Indonesian society, even in Purwokerto, almost all activities involve the help of the internet. PT Telkom as the largest internet service provider in Indonesia has facilitate the society to get internet access with its products, Indihome. Lately, a competitor is emerging which threatens the existence of PT Telkom as an internet service provider in Purwokerto, which is Biznet. Therefore, PT Telkom needs to examine what factors that make Indihome's customers loyal. Based on the problems above, this study was conducted to analyze the components of perceived product quality, perceived service quality, perceived value, and perceived price to the customer loyalty, mediated by customer satisfaction. The research methodology used for this study is a case study with survey research methods. The sample for this study were 155 people selected through convenience sampling technique derived from non-probability sampling technique. The sample comes from Indihome internet users in Purwokerto. The software used to analyze data is SPSS and AMOS statistical software. The research conclude that Perceived product quality, Perceived value, Perceived price has a positive effect on customer satisfaction. Perceived service quality has no effect on customer satisfaction. Customer satisfaction, Perceived service quality has a positive effect on customer loyalty. Perceived product quality, Perceived value, Perceived price has no effect on customer loyalty.